Facial recognition in multiple viewpoints - Muhammad Shahir Adha Mohd Zakaria (2019)
Faces we encounter in our daily lives are presented to us in several different views, yet most research on face recognition has focused on fixation points on the frontal orientation. This paper examines first fixation points by using eye-tracking technology to measure eye movements to seven different face orientations during a face recognition task. We found a significant shift in horizontal first fixation position towards the left of the face as the stimulus orientation increases towards the right. We also noted a significant decrease in face recognition performance at higher angles of orientation (60° and 90°), while no deficits in performance occurred between 0° (frontal orientation) and 40°. This paper also discusses this effect with regards to information distribution of face stimulus, perceptual learning and hemispherical asymmetry in face recognition.